2006
DOI: 10.1017/s0954579406060093
|View full text |Cite
|
Sign up to set email alerts
|

Leaders and followers in adolescent close friendships: Susceptibility to peer influence as a predictor of risky behavior, friendship instability, and depression

Abstract: Adolescents' susceptibility to peer influence was examined as a marker of difficulties in the general process of autonomy development that was likely to be related to deficits across multiple domains of psychosocial functioning. A laboratory-based assessment of susceptibility to peer influence in interactions with a close friend was developed and examined in relation to corollary reports obtained from adolescents, their mothers, and close peers at ages 13 and 14. As hypothesized, observed susceptibility to pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
222
1
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 216 publications
(242 citation statements)
references
References 43 publications
9
222
1
10
Order By: Relevance
“…In their study of early adolescents' susceptibility to peer influence, Allen and colleagues found no evidence of a moderating effect of gender, indicating that both males and females who scored higher on a generalized measure of susceptibility to peer influence were both at greater risk of early sexual behavior, externalizing behaviors and substance use (Allen et al 2006). Similarly, Miller (2009) found that, for both adolescent males and females, susceptibility to peer influence is a risk factor for delinquency.…”
Section: Who Are More Resistant To Deviant Peer Pressure: Males or Fementioning
confidence: 99%
See 1 more Smart Citation
“…In their study of early adolescents' susceptibility to peer influence, Allen and colleagues found no evidence of a moderating effect of gender, indicating that both males and females who scored higher on a generalized measure of susceptibility to peer influence were both at greater risk of early sexual behavior, externalizing behaviors and substance use (Allen et al 2006). Similarly, Miller (2009) found that, for both adolescent males and females, susceptibility to peer influence is a risk factor for delinquency.…”
Section: Who Are More Resistant To Deviant Peer Pressure: Males or Fementioning
confidence: 99%
“…Additionally, the desirability of engaging in risk-taking behaviors and succumbing to peer pressure may differ for males and females (Byrnes et al 1999;Closson 2009). Prior research has shown that adolescents who are more susceptible to peer pressure have more difficulty establishing social competence and have a harder time making their own judgments about risk-taking behaviors (Allen et al 2006). Similarly, Young et al (2009) qualitative study found that college females described their drinking patterns as motivated by pressure to make favorable impressions on their male peers.…”
Section: Who Are More Resistant To Deviant Peer Pressure: Males or Fementioning
confidence: 99%
“…Prior work examining the sequelae of negative peer pressure has linked peer pressure to a host of undesirable outcomes for adolescents, including greater alcohol consumption, cigarette use, petty theft, drug use, delinquency, depressive symptoms and poorer grades in school (Allen et al 2006;Santor et al 2000;Sullivan 2006). In addition to these consequences, Crockett et al (2006), using a longitudinal design to examine negative peer pressure at ages 12-13, found that pre-teens who experienced more negative peer pressure were also more likely to engage in risky sexual behavior at ages 16-17 as compared to teens who did not experience negative peer pressure when they were younger.…”
Section: Peer Pressure As a Form Of Autonomy Restrictionmentioning
confidence: 99%
“…Little research, however, has explored associations between negative peer pressure and future interpersonal relationships. In one exception, Allen et al 2006, found that negative peer influence predicted less stability in adolescents' friendships over a one-year period, indicating that peer pressure may indeed impact future relationships in important ways. Despite these initial indications, however, research has yet to address the potential influence of such peer pressure on adolescents' romantic relationships.…”
Section: Peer Pressure As a Form Of Autonomy Restrictionmentioning
confidence: 99%
“…This report is drawn from a larger longitudinal investigation of adolescent social development in familial and peer contexts (see Allen, Porter, & McFarland, 2006;Allen, Porter, McFarland, Marsh, & McElhaney, 2005). Participants included 185 adolescents who were initially interviewed at approximately age 13 (52% female; Age: M = 13.35, SD = 0.64) with their parents and closest friends, and then re-interviewed on an annual basis for the next 5-6 years.…”
Section: Participantsmentioning
confidence: 99%